2018
DOI: 10.31661/gmj.v7i0.1000
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis after Transplantation of Adipose Tissue-Derived Stem Cells in Azoospermic Guinea Pigs: A Histological and Histomorphometric Study

Abstract: Background: The purpose of this research was to determine histomorphometric changes in busulfan-induced azoospermia after transplantation of AdSCs in guinea pig. AdSCs were isolated from adipose tissue around the testes of guinea pigs and characterized for mesenchymal properties.Materials and Methods: Guinea pigs were allocated into three groups, including the control group without any intervention. To induce azoospermia, groups 2 and 3 received a dose of 40 mg/kg of busulfan with 21 days interval. Group 3 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Guinea pigs were exposed to the sGC dexamethasone 21‐phospate disodium salt in the drinking water (Dex; 3 mg/kg; Sigma Aldrich, St. Louis, MO) every other day for 48 days ( n = 6). This duration of exposure encompasses the entire spermatogenic process of the guinea pig 30 so that sperm were exposed to sGC at multiple stages of spermatogenesis as well as maturation during epididymal transit. Controls received untreated water ( n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Guinea pigs were exposed to the sGC dexamethasone 21‐phospate disodium salt in the drinking water (Dex; 3 mg/kg; Sigma Aldrich, St. Louis, MO) every other day for 48 days ( n = 6). This duration of exposure encompasses the entire spermatogenic process of the guinea pig 30 so that sperm were exposed to sGC at multiple stages of spermatogenesis as well as maturation during epididymal transit. Controls received untreated water ( n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…ADSCs and AFSCs can reduce oxidative stress in the testes and promote sperm production, ( Eliyasi et al, 2020 ; Ibrahim et al, 2021 ; Qian et al, 2020 ; Siregar et al, 2021 ), and can improve the damage of chemotherapy drugs to testes ( Meligy et al, 2019 ). Intratesticular injection of ADSCs can improve the spermatogenesis of azoospermia ( Ganjibakhsh et al, 2022 ; Hajihoseini et al, 2018 ; Karimaghai et al, 2018 ), while xenotransplantation of human umbilical cord blood derived MSCs into azoospermia mice also has the same effect ( Abd et al, 2017 ). Animal experiments have shown that after transplantation of BM-MSCs into the testis, in addition to influencing male reproductive function through paracrine action, they will also relocate to a new niche to form colonies, thus realizing the reconstruction of the damaged testicular germinal epithelium ( Ghasemzadeh-Hasankolaei et al, 2016 ; Monsefi et al, 2013 ).…”
Section: Main Textmentioning
confidence: 99%